Linha é dentro?: uma discussão sobre valores, esportes e significados - Sauerbronn, João Felipe Rammelt (2002)
The purpose of this work is to study how Brazilians living in Rio de Janeiro values sports products and practice. Using the typology proposed by Holbrook (1999), we had tried to identify sports consumer behavior in order to help building marketing strategies. The consumer value typology described can be used as a source of information useful not only to sports but also to entertainment organizations. The data analyzed were collected using deep interviews (McCracken, 1988). The experiential aspects of sports consumption and their relations to consumer behavior were explored during the interviews. Holbrook' s (1999) typology of consumer values was used to categorize sports consumer types. As observed, four of the types proposed by Holbrook (1999) are useful to describe subjects' sports consumer behavior.